European Translation Studies, Une science qui dérange, and Why Equivalence Needn’t Be a Dirty Word - Pym, Anthony (TTR)

(untitled) (Association canadienne de traductologie, 1995)
AbstractEuropean Translation Studies, Une science qui dérange, and Why Equivalence Needn't Be a Dirty Word -Debates about equivalence have marked the development of European translation studies since the 1970s, forming a significant frame for the institutional legitimation of the discipline. A brief survey of these debates, carried out in terms of Bourdieu's defence of sociology as an "upsetting" science, distinguishes between the precarious legitimation of linguistic-based equivalence in the 1970s and several target-side critiques directed at the concept in the 1980s. However, the alternative institutional legitimation associated with the critiques of equivalence may well have been conceptually desintegrative and intellectually mediocre. It is concluded that translation studies could now become properly upsetting by returning to equivalence and considering it as an operative illusion necessary for the definition and social function of any translation.